Bergmann glia modulate cerebellar Purkinje cell bistability via Ca 2+ -dependent K + uptake - Fushun Wang; Qiwu Xu; Weishan Wang; Takahiro Takano; Maiken Nedergaard (2012)
Recent studies have shown that cerebellar Bergmann glia display coordinated Ca 2+ transients in live mice. However, the functional significance of Bergmann glial Ca 2+ signaling remains poorly understood. Using transgenic mice that allow selective stimulation of glial cells, we report here that cytosolic Ca 2+ regulates uptake of K + by Bergmann glia, thus providing a powerful mechanism for control of Purkinje cell-membrane potential. The decline in extracellular K + evoked by agonist-induced Ca 2+ in Bergmann glia transiently increased spike activity of Purkinje cells in cerebellar slices as well as in live anesthetized mice. Thus, Bergmann glia play a previously unappreciated role in controlling the membrane potential and thereby the activity of adjacent Purkinje cells.